Arsenite-loaded nanoparticles inhibit the invasion and metastasis of a hepatocellular carcinoma: in vitro and in vivo study. (5th October 2017) - Chi, Xiaoqin; Yin, Zhenyu; Jin, Jianbin; Li, Hui; Zhou, Jian; Zhao, Zhenghuan; Zhang, Sheng; Zhao, Wenxiu; Xie, Chengrong; Li, Jie; Feng, Min; Lin, Hongyu; et al.
Abstract: Postoperative recurrence and metastasis are the major problems for the current treatment of hepatocellular carcinomas (HCC) in the clinic, including hepatectomy and liver transplantation. Here, we report that arsentic-loaded nanoparticles (ALNPs) are able to reduce the invasion of HCC cells in vitro, and, more importantly, can strongly suppress the invasion and metastasis of HCC in vivo without adverse side effects. Compared to free drug arsenic trioxide, ALNPs can deliver the drug into cancer cells more efficiently, destroy the structure of microtubules and reduce the aggregation of microfilaments in cell membranes more significantly. Furthermore, our results also reveal that tumor cells in murine blood were reduced remarkably after intravenous injection of ALNPs, indicating that this nano-drug may efficiently kill circulating tumor cells in vivo . In conclusion, our nano-drug ALNPs have great potential for the suppression of metastasis of HCC, which may open up a new avenue for the effective treatment of HCC without metastasis and recurrence.